2019
DOI: 10.1002/ejhf.1439
|View full text |Cite
|
Sign up to set email alerts
|

The novel butyrate derivative phenylalanine‐butyramide protects from doxorubicin‐induced cardiotoxicity

Abstract: AimsButyric acid (BUT), a short chain fatty acid produced daily by the gut microbiota, has proven beneficial in models of cardiovascular diseases. With advancements in cancer survival, an increasing number of patients are at risk of anticancer drug cardiotoxicity. Here we assess whether the novel BUT derivative phenylalanine-butyramide (FBA) protects from doxorubicin (DOXO) cardiotoxicity, by decreasing oxidative stress and improving mitochondrial function.In C57BL6 mice, DOXO produced left ventricular dilatat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 35 publications
1
71
0
Order By: Relevance
“…Treatment with butyrate attenuates fractional abdominal aorta ligation-stimulated myocardial hypertrophy, as confirmed by reduced collagen content and preservation of left ventricle systolic and diastolic dysfunction through reducing oxidative stress and increasing mitochondrial DNA concentration [119]. More interestingly, butyrate derivative phenylalanine-butyramide also protects against doxorubicin-stimulated cardiotoxicity through regulating oxidative stress and improving the function of mitochondria [120]. Therefore, butyrate serves as a cardioprotective factor partially via repressing oxidative stress.…”
Section: Butyrate and Butyrylationmentioning
confidence: 96%
“…Treatment with butyrate attenuates fractional abdominal aorta ligation-stimulated myocardial hypertrophy, as confirmed by reduced collagen content and preservation of left ventricle systolic and diastolic dysfunction through reducing oxidative stress and increasing mitochondrial DNA concentration [119]. More interestingly, butyrate derivative phenylalanine-butyramide also protects against doxorubicin-stimulated cardiotoxicity through regulating oxidative stress and improving the function of mitochondria [120]. Therefore, butyrate serves as a cardioprotective factor partially via repressing oxidative stress.…”
Section: Butyrate and Butyrylationmentioning
confidence: 96%
“…Therefore, DOX inevitably brings a series of anti‐cancer side effects, of which cardiac toxicity is the most highlighted and lethal. Numerous studies have reported the important role of redox cycling and ROS generation in DOX‐induced cardiotoxicity 19,29 . However, intervention with an ROS inhibitor failed to rescue cardiotoxicity, 19 which thereby suggests the existence of additional factors.…”
Section: Discussionmentioning
confidence: 99%
“…SCFA bind several transmembrane receptors, mediating effects on blood pressure, glucose homeostasis, appetite, obesity [94]. In particular, butyrate has long been recognized important to maintain gut barrier function and to exert beneficial effects when administered exogenously in several experimental models of CVD [95,96]. Recently, propionate has also been shown to significantly attenuate cardiac hypertrophy, fibrosis, vascular dysfunction, and hypertension in two different mouse models of hypertensive cardiovascular damage [97], even if its precise role in HF remains largely undetermined.…”
Section: Role Of Gut Microbiota In Hfmentioning
confidence: 99%